Advancing research on emergency care systems in low-income and middle-income countries: ensuring high-quality care delivery systems. (29th July 2019) - Moresky, Rachel T; Razzak, Junaid; Reynolds, Teri; Wallis, Lee A; Wachira, Benjamin W; Nyirenda, Mulinda; Carlo, Waldemar A; Lin, Janet; Patel, Shama; Bhoi, Sanjeev; Risko, Nicholas; Wendle, Lily A; et al.
Abstract : Emergency care systems (ECS) address a wide range of acute conditions, including emergent conditions from communicable diseases, non-communicable diseases, pregnancy and injury. Together, ECS represent an area of great potential for reducing morbidity and mortality in low-income and middle-income countries (LMICs). It is estimated that up to 54% of annual deaths in LMICs could be addressed by improved prehospital and facility-based emergency care. Research is needed to identify strategies for enhancing ECS to optimise prevention and treatment of conditions presenting in this context, yet significant gaps persist in defining critical research questions for ECS studies in LMICs. The Collaborative on Enhancing Emergency Care Research in LMICs seeks to promote research that improves immediate and long-term outcomes for clients and populations with emergent conditions. The objective of this paper is to describe systems approaches and research strategies for ECS in LMICs, elucidate priority research questions and methodology, and present a selection of studies addressing the operational, implementation, policy and health systems domains of health systems research as an approach to studying ECS. Finally, we briefly discuss limitations and the next steps in developing ECS-oriented interventions and research.